The relevance of social capital in efforts to develop entrepreneurship education - Herry Porda Nugroho Putro; Rusmaniah Rusmaniah; Mutiani Mutiani; Jumriani Jumriani; Bambang Subiyakto (Intelektual Pustaka Media Utama, 2022)
Universities in Indonesia create millions of graduates, but the labor market does not absorb most graduates, so they become unemployed. One of the ways to overcome unemployment is through entrepreneurship education to encourage them to become entrepreneurs to create their jobs. The success of entrepreneurship is determined by utilizing capital, one of which is social capital. This study aimed to find out how the relevance of social capital in developing entrepreneurship education. This was qualitative study, and data was gathered through in-depth interviews, observation, and documentation. Data analysis went through the stages of reduction, presentation, and conclusion drawing and was finally verified. The results of the research explained that the elements of social capital, including networks, norms, and trust was built through entrepreneurship education.